Accumulation of advanced oxidation protein products aggravates bone-fat imbalance during skeletal aging - Yu-Sheng Huang; Jia-Wen Gao; Rui-Feng Ao; Xin-Yu Liu; Di-Zheng Wu; Jun-Long Huang; Chen Tu; Jing-Shen Zhuang; Si-Yuan Zhu; Zhao-Ming Zhong (Journal of Orthopaedic Translation)
Background: Skeletal aging is characterized by a decrease in bone mass and an increase in marrowfat content. Advanced oxidation protein products (AOPPs) accumulate easily with aging and disrupt redox homeostasis. We examined whether AOPPs accumulation contributes to the bone-fat imbalance during skeletal aging. Methods: Both young and aged mice were employed to assess the changes of AOPPs levels and its contribution to bone-fat imbalance during skeletal aging. Primary bone marrow mesenchymal stromal cells (MSCs) were used to examine the potential role of AOPPs in age-related switch between osteogenic and adipogenic differentiation. Aged mice were also gavaged by non-selective antioxidant N‐acetyl‐L‐cysteine (NAC), followed by close monitoring of the changes in AOPPs levels and bone-fat metabolism. Furthermore, young mice were chronically exposed to AOPPs and then evaluated for the changes of bone mass and marrow adiposity. Results: The levels of AOPPs in serum and bone marrow were markedly higher in aged mice than that in young mice. Age-related accumulation of AOPPs was accompanied by reduced bone formation, increased marrow adiposity and deterioration of bone microstructure. Reduced AOPPs accumulation by antioxidant NAC leaded to improvement of the bone-fat imbalance in aged mice. Similarly, the bone-fat imbalance was induced by chronic AOPPs loading in young mice. Compared with MSCs from young mice, MSCs from aged mice tended to differentiate into adipocytes rather than osteoblasts and displayed cellular senescence. Exposure of primary MSCs to AOPPs resulted in the switch from osteogenic to adipogenic lineage and cellular senescence. AOPPs challenge also increased intracellular ROS generation by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and mitochondria. The antioxidant NAC, after scavenging ROS, ameliorated the AOPPs-induced lineage switch and senescence in MSCs by inhibiting the PI3K/AKT/mTOR pathway. Conclusion: Our findings revealed the involvement of AOPPs in age‐related switch between osteogenic and adipogenic differentiation, and illuminated a novel potential mechanism underlying bone-fat imbalance during skeletal aging. The translational potential of this article: Reducing AOPPs accumulation and its cascading effects on MSCs might be an attractive strategy for delaying skeletal aging.